Using Behavior Sequence Analysis to Map Serial Killers’ Life Histories - Keatley, David A. (Journal of interpersonal violence, 2021)
The aim of the current research was to provide a novel method for mapping the developmental sequences of serial killers’ life histories. An in-depth biographical account of serial killers’ lives, from birth through to conviction, was gained and analyzed using Behavior Sequence Analysis. The analyses highlight similarities in behavioral events across the serial killers’ lives, indicating not only which risk factors occur, but the temporal order of these factors. Results focused on early childhood environment, indicating the role of parental abuse; behaviors and events surrounding criminal histories of serial killers, showing that many had previous convictions and were known to police for other crimes; behaviors surrounding their murders, highlighting differences in victim choice and modus operandi; and, finally, trial pleas and convictions. The present research, therefore, provides a novel approach to synthesizing large volumes of data on criminals and presenting results in accessible, understandable outcomes.